2018
DOI: 10.1109/lpt.2018.2811411
|View full text |Cite
|
Sign up to set email alerts
|

Interrogation of Ultra-Weak FBG Array Using Double-Pulse and Heterodyne Detection

Abstract: A high performance interrogation method for ultra-weak FBG (UWFBG) using double-pulse and heterodyne detection method is proposed. The perturbation along the UWFBG array is located quickly through the use of double-pulsed optical input waveform. Then the perturbation of fiber is quantified precisely by demodulating the phase of differential signals from a heterodyne configuration. The efficiency of measuring the perturbation is improved by more than 20 times than that of using single probe pulse. In comparison… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…Among all fiber optic sensors, fiber Bragg grating (FBG) sensors are well-known for its reliability, high sensitivity, and the ease in installation [38,39]. The relatively low cost of FBG sensors made large-scale application practical [38,[40][41][42][43] and the chemical inertness of the FBG sensors made them great candidates in corrosion monitoring systems. A few recent attempts to apply FBG sensors in corrosion monitoring of steel rebar in reinforced concrete had shown the possibility of FBG sensors in corrosion monitoring [36,[44][45][46][47].…”
Section: Introductionmentioning
confidence: 99%
“…Among all fiber optic sensors, fiber Bragg grating (FBG) sensors are well-known for its reliability, high sensitivity, and the ease in installation [38,39]. The relatively low cost of FBG sensors made large-scale application practical [38,[40][41][42][43] and the chemical inertness of the FBG sensors made them great candidates in corrosion monitoring systems. A few recent attempts to apply FBG sensors in corrosion monitoring of steel rebar in reinforced concrete had shown the possibility of FBG sensors in corrosion monitoring [36,[44][45][46][47].…”
Section: Introductionmentioning
confidence: 99%
“…Heterodyne detection could provide gain to the photoelectric conversion process and improve the receiving sensitivity, which results in longer sensing distance. Liu et al [55] reported a high performance interrogation system for the UWFBG array using the double-pulse and a heterodyne detection method.…”
Section: Ultra-weak Fbgsmentioning
confidence: 99%
“…It can achieve a fiber length variation sensitivity of 117 pm/√Hz with a distance between WFBGs equal to 99 m [ 38 ]. Investigations of vast arrays of WFBG were carried out in a laboratory: setup with 964 WFBGs for nε-scale deformation measurements [ 40 ], 90 WFBGs helped to detect 14.63 nm deformations of 50 m fiber between neighboring reflectors [ 41 ]. Parallel measurements using traditional sensors were carried out: phi-OTDR system with 660 WFBGs was compared to geophones and showed good agreement in signal shape [ 42 ].…”
Section: Introductionmentioning
confidence: 99%